Geomorphology and stratigraphy area river basin Mishca (Canarias district, province of Victor Fajardo, Ayacucho department) - Castañeda Zavaleta, Marko Eduardo (2013)
The high parts of Mishca river basin located in the province Victor Fajardo, district Canarias of Ayacucho department, morpho-logically is located at interandean valleys sector; geologically in the western side of Eastern Cordillera, whose main structural dominium belongs to units from Paleozoic and Mesozoic Ages, with the litostratigraphic units: Mitu Group (Upper Permian- Triassic), Pucara Group (Upper Triassic-LowerJurassic), Chunumayo Formation (Middle Jurassic); magmaticactivity is represented locally by Querobamba Granite related to Upper Paleozoic magmatic cycle.